Antifungal Activity of Resveratrol against Botrytis cinerea Is Improved Using 2-Furyl Derivatives - Caruso, Francesco; Mendoza, Leonora; Castro, Paulo; Cotoras, Milena; Aguirre, Maria; Matsuhiro, Betty; Isaacs, Mauricio; Rossi, Miriam; Viglianti, Angela; Antonioletti, Roberto (PLOS ONE, 2011)
The antifungal effect of three furyl compounds closely related to resveratrol, (E)-3,4,5-trimethoxy-β-(2-furyl)-styrene (1), (E)-4-methoxy-β-(2-furyl)-styrene (2) and (E)-3,5-dimethoxy-β-(2-furyl)-styrene (3) against Botrytis cinerea was analyzed. The inhibitory effect, at 100 µg ml−1 of compounds 1, 2, 3 and resveratrol on conidia germination, was determined to be about 70%, while at the same concentration pterostilbene (a dimethoxyl derivative of resveratrol) produced complete inhibition. The title compounds were more fungitoxic towards in vitro mycelial growth than resveratrol and pterostilbene. Compound 3 was the most active and a potential explanation of this feature is given using density functional theory (DFT) calculations on the demethoxylation/demethylation process. Compound 3 was further evaluated for its effects on laccase production, oxygen consumption and membrane integrity of B. cinerea. An increase of the laccase activity was observed in the presence of compound 3 and, using Sytox Green nucleic acid stain, it was demonstrated that this compound altered B. cinerea membrane. Finally, compound 3 partially affected conidia respiration.